Efeito gastroprotetor das folhas de Solanum Stipulaceum Willd ex. Roem & Shult (sacatinga) - Lima, Cirlane Alves Araujo de (2023)
Solanum stipulaceum (sacatinga) is an endemic species native to Brazil, recommended for its traditional use in the Vila Capim Arapiraca-AL Village for the treatment of gastric ulcers. The objectives of the present study were to identify the compounds of the chloroform extract (CE) and evaluate their potential affinities to binding sites of endogenous mediators involved in the secretion of acid and gastric mucus through the in silico model by molecular docking, in addition to evaluating the antioxidant and antiulcer activity of CE and chloroform fraction (CF), histologically analyze the gastric tissue of animals treated in the acute ulcer experiment, as well as the mechanism(s) of action involved in the activity antiulcer. The components of the CE were identified by high-performance liquid chromatography coupled to a mass spectrometer (HPLC/MS) and then a computational simulation of the docking was performed by molecular docking. The antioxidant activity of CE and CF was evaluated using the DPPH• , ABTS•+ and β-carotene in vitro methods. The gastroprotective effect of CE (10, 30 and 100, 300 and 500 mg/kg), CF (200 mg/kg) and the compound N-trans-feruloyltyramine (NTF) (10 and 50 mg/kg) were evaluated in the model of acute gastric ulcer induced by acidified ethanol in male Swiss mice. The effect of CE (300 mg/kg) and CF (200 mg/kg) on gastric secretion and mucus production were evaluated in the pylorus ligation model. The participation of prostaglandins (PG), the involvement of ATP-sensitive K+ channels (KATP), the formation of nitric oxide (NO) and the involvement of non-protein sulfhydryl groups (NP-SH) were investigated in the ulcer model, described previously. The results of the spectroscopic analysis by HPLC/MS identified 10 CE compounds, among these, NTF was the one that showed the best interaction with two of the receptors of interest the EP3 receptor and the proton pump (H+ /K+ ATPase) in the molecular docking assay. The CF presented a higher content of phenolic compounds (191.5±2.0 mg EAG/g of the fraction) when compared to the CE (42.53±4.0 mg EAG/g of the extract). In antioxidant tests, both CE and CF showed significant activity in all models. CE (300 and 500 mg/kg), CF (200 mg/kg) and NTF (10 and 50 mg/kg) showed a significant gastroprotective effect, with a percentage of inhibition of (56.1% and 64.2%), (77.2%) and (61.8% and 56.2%), respectively, in addition to reducing histological changes characteristic of the ulcer. In the pylorus ligation test, CE (300 mg/kg) and CF (200 mg/kg) increased mucus production by 206% and 141.3%, respectively; reduced gastric volume by 77% and 92.6% and increased pH by 31.4% and 98%, respectively, but did not reduce total acidity. Pretreatment with a prostaglandin synthesis inhibitor (indomethacin, 10 mg/kg i.p.), with a nitric oxide synthesis inhibitor (LNAME, 70 mg/kg i.p.), with an ATP-dependent potassium channel blocker (glibenclamide, 10 mg/kg i.p.) and the sulfhydryl group blocker (N-ethylmaleimide, 10 mg/kg i.p.) inhibited the gastroprotective response caused by CE and CF. These results provide evidence that compounds from S. stipulaceum exert gastroprotective action by increasing the formation of prostaglandins, nitric oxide and sulfhydryl groups and activating potassium channels resulting in antisecretory activity and increased production of gastric mucus.